2013
DOI: 10.5194/bg-10-3349-2013
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion of coastal waters into the pelagic eastern Mediterranean: in situ and satellite-based characterization

Abstract: A combined dataset of near-real-time multi-satellite observations and in situ measurements from a high-resolution survey is used for characterizing physical-biogeochemical properties of a patch stretching from the coast to the open sea in the Levantine Basin (LB) of the eastern Mediterranean (EM). Spatial analysis of the combined dataset indicates that the patch is a semi-enclosed system, bounded within the mixed layer and separated from ambient waters by transport barriers induced by horizontal stirring. As s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…The correlation with the OW parameter, which is a measure to morphology of mesoscale eddies as observed in a satellite‐derived velocity field [ Lehahn et al ., ], indicates that aerosol concentrations varied in space in response to mesoscale oceanic variability at the vicinity of eddy A . This is supported by the fact the leg included crossing of LCS (Figure b), which may separate between water bodies with distinct physical and biogeochemical characteristics [ Lehahn et al ., ; d ' Ovidio et al ., ; Efrati et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…The correlation with the OW parameter, which is a measure to morphology of mesoscale eddies as observed in a satellite‐derived velocity field [ Lehahn et al ., ], indicates that aerosol concentrations varied in space in response to mesoscale oceanic variability at the vicinity of eddy A . This is supported by the fact the leg included crossing of LCS (Figure b), which may separate between water bodies with distinct physical and biogeochemical characteristics [ Lehahn et al ., ; d ' Ovidio et al ., ; Efrati et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, relatively high concentrations of biogenic silica were found in some areas, perhaps related to the presence of eddies (Crombet et al, 2011). High silica in a filament stretching from the coast to the open sea in the Levantine Basin were reported as well (Efrati et al, 2013) (Fig. 20).…”
Section: Present Knowledgementioning
confidence: 95%
“…One potentially important process which has not been included in this budget is the effect of silica cycling processes in coastal areas. Recently it was shown that Si is advected from the shore towards the open sea in the easternmost part of the Mediterranean (Efrati et al, 2013). If silicic acid from diagenesis on the continental shelf is advected from the coastal shelf into the offshore waters, it will represent a new source of silicic acid which will be exported from the basin.…”
Section: Total Silica Budget For the Emsmentioning
confidence: 99%